PERANAN LAPIS GAMBUT TERHADAP MOBILITAS KARBON ORGANIK TERLARUT DAN PELEPASAN ION FE DAN AL PADA TANAH GAMBUT BERSUBSTRATUM BAHAN SULFIDIK - Damanik Z; Purwanto B.H.; Hanudin E.; Radjagukguk B. (AgriPeat, 2015)
The objectives of this study was to investigate the role of peat layer in the mobility of DOC and the release of toxic elements from the underlying sulphidic materials for the various peat thicknesses. The study was conducted in the soil department greenhouse, Faculty of Agriculture, Gadjah Mada University from July to August 2015The experiment conducted in soil column made from PVC pipe which have different peat layer thicknesses (without peat layer, < 50 cm, and 50-100 cm). Leaching was conducted every week, with 500 cc distilled water for 4 weeks. Filtrate was collected, and pH, dissolved organic carbon, and Fe and Al ions was analyzed. The results of the study showed that diminution of thickness of the peat stratum of the soils underlaid by sulphidic material substratum caused the release, and mobilization of Fe2+ and Al3+- ions along with leaching water which might have a significant impact in decreasing the quality of the surrounding water environments in the form of acidification, and enrichment of Fe2+ and Al3+ ions. In addition to the impact of the thickness of the peat stratum, quality of the leaching water was also determined by the quality of the peat material, primarily the degree of decomposition, and concentration of DOC which played the role of chelating agent for toxic ions such as Fe and Al